One-pot decarboxylation and decarbonylation reaction of waste cooking oil over activated carbon supported nickel-zinc catalyst into diesel-like fuels - Wan Khalit, Wan Nor Adira; Mijan, N. Asikin; Tengku Sharifah Marliza; Gamal, M. Safa; Shamsuddin, Mohd Razali; I., Nur Azreena; Saiman, Mohd Izham; Y. H., Taufiq Yap (Elsevier BV, 2022)
In this work, green diesel was generated via one-pot decarboxylation/decarbonylation (deoxygenation) reactions over a series of Ni20Znx/AC (X: 5–20 wt%) catalysts. The Ni20Zn10/AC catalyst exhibited superior deoxygenation reaction by yielding 86% hydrocarbons and 79% of n-(C15 + C17) selectivity, with the activity tending to undergo the decarbonylation pathway. Indeed, high deoxygenation activity is correlated with a higher acidity and basicity strength of the catalyst, and the removal of the oxygenates species occurred via decarbonylation pathways. The Ni20Zn10/AC catalyst showed a promising catalytic longevity and recyclability up until four runs, with a hydrocarbon yield of 78–87% and n-(C15 + C17) selectivity within the range of 43–70%. The decrease in the n-(C15 + C17) selectivity at the fourth cycle was due to leaching of active metal and the coking activity. The fuel properties of the green diesel (G100) were investigated, and it was revealed that the green diesel almost exhibited outstanding fuel properties (acid value, kinematic viscosity, flash point, cetane index, and calorific value) in comparison with ultra-low sulfur diesel (ULSD), suggesting that G100 can be used in vehicle engines without modification and has great potential for commercialization.